Analisis Kebijakan Pendidikan Full Day School dalam Pembentukan Karakter Anak - Hikmah, Nur; Yuspiani, Yuspiani; Baharuddin, Baharuddin (MAN 4 Kota Pekanbaru, 2024)
This research aims to analyze the full day school policy at Al Bashirah Private Madrasah Ibtidaiyah (MIS) and its impact on student character formation. With a qualitative approach and case study design, data was collected through in-depth interviews, observation and documentation from school principals, teachers, students and parents. The research results show that the implementation of Full day school at MIS Al Bashirah was successful in improving students' character values, especially discipline, responsibility and religiosity. Students show positive developments in their attitudes and behavior, which is reflected in active participation in academic and religious activities. However, this research also found several challenges, including effective time management and limited supporting facilities. Therefore, although this policy has the potential to strengthen character formation, adjustments need to be made so as not to burden students physically and mentally. It is hoped that this research can contribute to the development of character education policies in religious-based school environments.